2014
DOI: 10.1002/2013tc003487
|View full text |Cite
|
Sign up to set email alerts
|

Changes in paleostress state along a subduction zone preserved in an on-land accretionary complex, the Yokonami mélange in the Cretaceous Shimanto Belt, Kochi, southwest Japan

Abstract: A change in paleostress along a subduction zone plate interface in the shallow portion of a seismogenic zone was detected in an on-land accretionary complex, the Yokonami mélange in southwest Japan, using the microfault inversion method. Microfaults were classified into two groups based on location: those occurring throughout the Yokonami mélange and those occurring in the Goshikinohama fault zone, which is considered to be a fossil seismogenic fault and is located at the northern end of the Yokonami mélange. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…Schematic model of temporal–spatial changes in stress regime within a subduction zone. Left panel shows the relatively long‐term stress state along the décollement ( DC ) (after Hashimoto et al, ) and on the megasplay fault (in this study, related to subduction during the pre‐seismic period). Right panel shows the post‐seismic stress regime after a large earthquake, due to a drop in shear stress along the megasplay fault (Otsubo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schematic model of temporal–spatial changes in stress regime within a subduction zone. Left panel shows the relatively long‐term stress state along the décollement ( DC ) (after Hashimoto et al, ) and on the megasplay fault (in this study, related to subduction during the pre‐seismic period). Right panel shows the post‐seismic stress regime after a large earthquake, due to a drop in shear stress along the megasplay fault (Otsubo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reconstructed the paleostresses along subsurface faults (e.g. Dezayes, Villemin, Genter, Traineau, & Angelier, ; Hashimoto, EidA, & Ueda, ; Lallemant, Byrne, Maltman, Karig, & Henry, ; Martin & Bergerat, ; Otsubo, Shigematsu, Kitagawa, et al, ; Rocher, Lacomb, Angelier, Deffontaines, & Verdier, ; Yamada & Yamaji, ). However, to fully characterize the paleostress history, inversion and models must account for heterogeneous fault slip data.…”
Section: Introductionmentioning
confidence: 99%
“…Neither data set shows stress permutations where the principal stresses switch multiple times, for example over several earthquake cycles. At least two explanations are possible, either: 1) all of the late stage normal faults formed after the last earthquake (e.g., after 1944) due to stress relaxation and stress permutations or 2) the stress states vary during the seismic cycle (e.g., 1 alternates between horizontal and vertical from one cycle to the next) (Wang and Hu, 2006;Conin et al, 2012;Kinoshita and Tobin, 2013;Sacks et al, 2013;Hashimoto et al, 2014), but during an earthquake, failure is accommodated only or primarily by slip…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Recently, changes in stress field resulting from large earthquakes were documented for the 1999 Chi‐Chi earthquake, Taiwan [ Lin et al ., ], and the 2011 Tohoku‐Oki earthquake, northeast Japan [ Hasegawa et al ., ; Lin et al ., ]; the changes were determined by remotely sensing observations or direct measurements from borehole logs. If such temporal changes in paleostress related to large earthquakes are considered to have occurred commonly in the past and are expected in the future as well, they can be determined from the slip data of microfaults in the outcrops or drilled cores even though the microfaults have been integrally activated by a number of seismic event [ Hashimoto et al ., ]. Hashimoto et al .…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto et al . [] found a switch in paleostress in an exhumed accretionary complex and suggested that the stress switch could be related to a change in stress by seismic cycles in the subduction zone. However, the studies by these authors did not include any information about the stress magnitude.…”
Section: Introductionmentioning
confidence: 99%